Application of A Contextual Approach to Students' Learning Outcomes in Pandemic Times - Siti Habibah Noor Saadah; Wikanengsih Wikanengsih; Enung Nurhayati (IKIP Siliwangi, 2022)
ABSTRACTIn the interest of increasing student understanding, teachers are expected to be able to select and sort out various methods, models, and approaches that are appropriate to current circumstances. Applying an appropriate learning approach is expected to minimize boredom in learning activities. The purpose of this study is that teachers are expected to be able to apply a contextual approach to the learning outcomes that will be obtained by students. The method used in this research is descriptive statistical analysis, which describes learning outcomes through data in the form of diagrams taken from several student questionnaires and teacher interviews. The results showed that students' understanding of the material before applying the contextual approach to learning outcomes was the limited understanding of students regarding the description text material. It can be concluded that the application of the contextual approach for students needs to be improved again.ABSTRAKDemi kepentingan meningkatkan pemahaman peserta didik, guru diharapkan mampu memilih dan memilah berbagai metode, model maupun pendekatan yang sesuai dengan keadaan saat ini. Dengan menerapkan pendekatan pembelajaran yang sesuai diharapkan dapat meminimalisir rasa bosan terhadap kegiatan pembelajaran. Tujuan dari penelitian ini adalah guru diharapkan dapat menerapkan pendekatan kontekstual terhadap hasil belajar yang akan diperoleh peserta didik. Metode yang digunakan dalam penelitian ini analisis statistik deskriptif, yaitu mendeskripsikan hasil belajar melalui data berupa diagram yang diambil dari angket sejumlah siswa dan wawancara guru. Hasil penelitian menunjukkan bahwa pemahaman peserta didik akan materi sebelum penerapan pendekatan kontekstual terhadap hasil belajar yaitu keterbatasannya pemahaman peserta didik terkait materi teks deskripsi. Dapat disimpulkan bahwa penerapan pendekatan kontekstual bagi peserta didik perlu ditingkatkan kembali.